2021
DOI: 10.1002/adsc.202100811
|View full text |Cite
|
Sign up to set email alerts
|

Cp*Co(III)‐Catalyzed Dehydrative C2‐Prenylation of Pyrrole and Indole with Allyl Alcohols

Abstract: Non-activated allyl alcohols are utilized as allylating agent for thiocarbamate-directed allylation of pyrrole and indole. The synthetic methodology is accompanied by advantages like silver-free conditions and generates water as the by-product. A wide range of substituted pyrroles and indoles along with several structurally different allyl alcohols took part in the reaction. Among notable examples, biologically relevant prenylation, geranylation, and synthesis of 1,3-dienes are achieved. Selective mono allylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Prenylating reagent plays a significant function in bioactive and synthetic substances because it has a high binding affinity for proteins and increases membrane permeability, enhancing bioactivity and bioavailability of prenylated drugs. Through a specific prenyl-binding domain, the prenyl group plays an important role in proteinprotein binding [22,23].…”
Section: Reagents For Prenylation Reaction and Their Applicationsmentioning
confidence: 99%
“…Prenylating reagent plays a significant function in bioactive and synthetic substances because it has a high binding affinity for proteins and increases membrane permeability, enhancing bioactivity and bioavailability of prenylated drugs. Through a specific prenyl-binding domain, the prenyl group plays an important role in proteinprotein binding [22,23].…”
Section: Reagents For Prenylation Reaction and Their Applicationsmentioning
confidence: 99%
“…[16] Later, the scope was expanded to allylation of benzamides and 6-arylpurines, [17] as well as indoleand pyrrolecarbothioamides. [18] Related examples of allylation of arenes with tertiary allyl amines [19] and with fluorinated alkenes [20] have been also described. In these cases, the mechanism would proceed via CÀ H metalation, alkene insertion, and β-heteroatom-elimination, which would be detrimental to the atom economy of the reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Matsunaga and Kanai demonstrated that unactivated allyl alcohols can also be used in the allylation reaction of N ‐(pyrimidin‐2‐yl)‐1 H ‐indoles [16] . Later, the scope was expanded to allylation of benzamides and 6‐arylpurines, [17] as well as indole‐ and pyrrolecarbothioamides [18] . Related examples of allylation of arenes with tertiary allyl amines [19] and with fluorinated alkenes [20] have been also described.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, C2 substituted indoles are also ubiquitous in various natural products and pharmaceuticals . Recently, transition-metal-catalyzed directed indoles C2 alkylation with alkenes has been developed but without reports on conjugated alkenes. In consideration of the importance of these alkynyl- and indole-containing molecules, we hope to develop an efficient method to achieve three-component cross-coupling of conjugated alkenes with electrophilic alkynylating reagent and indoles (Scheme C).…”
mentioning
confidence: 99%